Organizational and Economic Mechanism of Government in the Development of Tourist-Recreational Complexes - Sirojiddinov, Uktam Samaridinovich; Shodiyev, Kamoliddin (European Journal of Life Safety and Stability (2660-9630), 2021)
The article examines the physiological, medical, socio-economic processes of organizing modern leisure. If we look at the meanings of the terms "recreation" and "tourism" separately, it is not difficult to understand that "recreation" has a deeper meaning. At the same time, these phrases complement each other, creating a unique meaning and content. Therefore, in this study, we preferred to use the terms "tourist rest" or "recreational tourism". Recreational tourism is a trip organized for the purpose of rest, recovery, treatment, development of the physical, mental and emotional forces of a person. Recreational tourism is characterized by long journeys, mostly with fewer visits to one place and other dating sites.